Familial Melanoma Phenotype With Xeroderma Pigmentosum Group C (XP-C) Genotype - The Putative Role of MC1R Polymorphism as Modifier - Franciele Antonieta Bianchi Leidenz; Flavia Vasques Bittencourt; Williana Garcia Braga; Ellio Magno de Sá Araujo; Carolina Cavalieri Gomes; Vanessa de Fatima Bernardes; Eitan Friedman; Luiz De Marco (Mattioli1885, 2024)
Introduction: Xeroderma pigmentosum (XP), a rare inherited condition, hallmarked by extreme sensitivity to sun exposure resulting in multiple skin cancers and non-malignant skin alterations is attributed to homozygous inactivating pathogenic variants (PVs) in DNA repair genes, predominantly the XPC gene. Objectives: Report a unique phenotypic expression of mutant XPC allele that may be compatible with a putative modifier role for MC1R polymorphism. Methods: A family of 13 siblings, seven of whom were diagnosed with at least one cutaneous  melanoma (N = 53) and non-melanoma skin cancers (N = 9) was studied. Of seven melanoma-affected cases, five consented for genetic analysis. CDKN2A revealed no PV in any case and subsequent whole-exome sequencing (WES) identified a rare homozygous missense PV (c.919C>T; p.Arg307Trp) in exon 8 of the XPC gene in all affected individuals. Notably, XPC PV carriers who co-harbored the p.I155T MC1R variant (N = 3) exhibited larger number of tumors, deeper Breslow indexes, higher rates of invasive melanomas and earlier age at diagnosis compared with non MC1R variant carriers (N = 2). Conclusions: Familial malignant melanoma phenotype may, in fact, be an unusual clinical presentation of XPC, and MC1R may be a genetic modifier of penetrance and phenotype of mutant XPC alleles.